An Ultrasonographic Analysis of the Deep Inferior Tendon in the Masseter Muscle: Implications for Botulinum Toxin Injections - Jia Shi; Chenyang Li; Jinbo Zhou; Xinyu Guo; Guo Li; Meng You (Toxins)
(1) Background: With the increasing aesthetic pursuit of facial features, the clinical use of Botulinum Toxin Type A (BoNT-A) injections for masseter hypertrophy has been on the rise. However, due to variations in masseter muscle structure and differences in clinicians’ injection techniques, blind injections may lack precision, potentially compromising treatment accuracy and increasing the risk of complications. (2) Objectives: The study aims to use ultrasonography to detail the deep inferior tendon (DIT) within the masseter muscle in a young Chinese cohort, refine its classification, analyze muscle belly thickness and variations across groups, and propose a customized ultrasound-guided BoNT-A injection protocol. (3) Methods: Ultrasound imaging was used to observe the bilateral masseter muscles at rest and during clenching. The features of the DIT were classified from these images, and the thickness of the masseter’s distinct bellies associated with the DIT types was measured in both states. (4) Results: The study cohort included 103 participants (27 male, 76 female), with 30 muscles in the normal masseter group and 176 muscles in the hypertrophy group. The DIT was categorized as Type A, B (subtypes B1, B2), and C. The distribution of these types was consistent across normal, hypertrophic, and gender groups, all following the same trend (B > A > C). In hypertrophy, Type B1 showed uniform thickness across masseter bellies, B2 presented with a thinner intermediate belly, and Type C had mainly superficial muscle enlargement. Changes in muscle thickness during clenching were noted but not statistically significant among different bellies. (5) Conclusions: The study evidences individual variation in the DIT, highlighting the importance of precise DIT classification for effective BoNT-A injections. A tailored ultrasound-guided BoNT-A injection strategy based on this classification may enhance safety and efficacy of the therapy.